2021
DOI: 10.1272/jnms.jnms.2021_88-402
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Dominance of the Nitric Oxide Fractions Nitrate and Nitrite in the Epilepsy-Prone EL Mouse Brain

Abstract: Background: Oxidative stress is thought to be closely related to epileptogenesis. We have previously reported that nitric oxide (NO) levels are higher in epilepsy-prone EL mice between the ages of 3 and 8 weeks than in control mice. However, NO is divided into two fractions, nitrite (NO2) and nitrate (NO3), which appear to play different roles in epileptogenesis.Methods: NO2 and NO3 levels were measured, in EL mice and the control mice, in the parietal cortex, which is thought to be the primary epileptogenetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…In the present study, the results showed a decrease in the GSH and an increase in NO serum levels following PTZ injection. The present study, similar to various prior studies, showed that the injection of PTZ in animal models increases OS and NO and decreases antioxidant levels (Hosseini et al 2021;Kawakami et al 2021;Kumar et al 2018). Glutathione as an antioxidant helps protect cells against free radical damage.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, the results showed a decrease in the GSH and an increase in NO serum levels following PTZ injection. The present study, similar to various prior studies, showed that the injection of PTZ in animal models increases OS and NO and decreases antioxidant levels (Hosseini et al 2021;Kawakami et al 2021;Kumar et al 2018). Glutathione as an antioxidant helps protect cells against free radical damage.…”
Section: Discussionsupporting
confidence: 91%
“…People with atherosclerosis, diabetes, and high blood pressure often manifest NO pathway disorders (Ghimire et al 2017). NO has also been reported to be increased in PTZ-induced seizures (Kawakami et al 2021). The effects of ASE on NO and GSH have not been reported in the status epilepticus condition, but in a previous study, ASE modulate inducible NOS (iNOS) and protected porcine coronary endothelial cells against oxidative stress by preventing ROS production and GSH loss (Grossini et al 2014).…”
Section: Discussionmentioning
confidence: 99%